Transformações socioespaciais recentes no setor leste da cidade de Uberlândia-MG - Batista, Ivone Tavares (2018)
The objective of this dissertation was to systematize a set of data and information on socio-spatial transformations of the East Sector in the city of Uberlândia-MG, having specific objectives: to characterize the territorial formation of the Eastern Sector; identify the formation of regular and irregular allotment of this Sector; characterize real estate market trends in the Eastern Sector of the last ten years; to analyze the role of the creating large real estate projects in the Eastern Sector of the city with emphasis on the Granja Marileusa project and its possible impacts. The procedures used were: data / information collection from the Municipal Planning Department of Uberlândia on the occupation of the Eastern Sector; survey of data on the real estate market in the city of recent years; urban legislation and its changes in recent years; data collection and information on the Granja Marileusa development; survey of photographs, aerial photographs, files and projects of the Department of Urban Planning of the Municipality and mapping of the information. It was discovered that the Algar Group has partnered with major national and international companies to invest in areas that have been empty for decades. Impacts on urban mobility are felt around the enterprise. The eastern sector presents great internal diversity and this fact raises questions about the criteria of division of the city for planning purposes, taking the urban territorial sectors as a space cut for the actions of the public power and the various economic agents.